The role of exchange rate for current account: A panel data analysis - Flavio Vilela Vieira; Ronald MacDonald (EconomiA, 2020)
The goal of this paper is to address the role of the real effective exchange rate (fundamentals, misalignment and volatility) for the current account using a panel data analysis for a set of 58 countries, over the period of 1994-2014. The results suggest that exchange rate misalignment is relevant for current account adjustment where countries with a more appreciated (depreciated) exchange rate face a worse (better) current account performance. Regarding the role of other control variables, current account adjustment is affected by the savings rate where higher (lower) values are associated with better (worse) current account performance, corroborating the lessons from the consumption smoothing approach. There is also evidence of a positive effect for the lagged current account (persistence effect). For emerging and less developed countries, there is evidence of a significant role played by monetary independence where more (less) monetary independence is associated with better (worse) current account performance.
Keywords: F32; F41; C23; 330; Current account; Exchange rate; Panel data